The hepatitis E virus capsid protein ORF2 counteracts cell-intrinsic antiviral responses to enable persistent replication in cell culture - Mehnert, Ann-Kathrin; Stegmaier, Sebastian; Ramirez, Carlos; Toprak, Elif; Gonçalves Magalhães, Vladimir; Siebenkotten, Carla; Hu, Jungen; Simões Costa, Ana Luísa; Kirrmaier, Daniel; Knop, Michael; Wu, Xianfang; Tubiana, Thibault; et al. (PLoS pathogens, 2025)
Hepatitis E virus (HEV) is a significant human pathogen causing both acute and chronic infections worldwide. The cell-intrinsic antiviral response serves as the initial defense against viruses and has been shown to be activated upon HEV infection. HEV can replicate in the presence of this response, but the underlying mechanisms remain poorly understood. Here, we investigated the roles of the structural proteins ORF2 and ORF3 in the cell-intrinsic antiviral response to HEV infection. Mechanistically, we validated that ectopic ORF2, but not ORF3, interfered with antiviral and inflammatory signaling downstream of pattern recognition receptors, in part through interaction with the central adaptor protein TANK binding kinase 1. In the full-length viral context, ORF2 contributed to a reduced antiviral response and consequently, more efficient viral replication. In addition, we discovered a protective mechanism mediated by ORF2 that shielded viral replication from antiviral effectors. Using single-cell RNA-sequencing, we confirmed that the presence of ORF2 in infected cells dampened antiviral responses in both actively infected cells and bystanders. As a consequence, we found that early in the infection process, the progression of authentic HEV infection relied on the presence of ORF2, facilitating a balance between viral replication and the antiviral response. Altogether, our findings shed new light on the multifaceted role of ORF2 in the HEV life cycle and improve our understanding of the determinants that contribute to persistent HEV replication in cell culture.